Spastin Interacts with CRMP2 to Regulate Neurite Outgrowth by Controlling Microtubule Dynamics through Phosphorylation Modifications - Li, Sumei; Zhang, Jifeng; Zhang, Jiaqi; Li, Jiong; Cheng, Longfei; Chen, Li; Cha, Caihui; Guo, Guoqing (CNS & Neurological Disorders - Drug Targets, 2021)
Aims: Our work aims to revealing the underlying microtubule mechanism of neurites outgrowth during neuronal development and also proposes a feasible intervention pathway for reconstructing neural network connections after nerve injury. Background: Microtubule polymerization and severing form the basis for neurite outgrowth and branch formation. However, the mechanisms that underlie the dynamic instability of microtubules are unclear. Here, we showed that neurite outgrowth mediated by collapsing response mediator protein 2 (CRMP2) can be enhanced by spastin, which had an effect on the severing of microtubule cytoskeleton. Objective: To explore whether neurite outgrowth was mediated by coordination of CRMP2 and spastin. Methods: Hippocampal neurons were cultured in vitro in 24-well culture plates for 4 days before being used to perform the transfection. Calcium phosphate was used to transfect the CRMP2 and spastin constructs and their control into the neurons. An interaction between CRMP2 and spastin was examined by using pull down, CoIP and immunofluorescence colocalization assays. And immunostaining was also performed to determine the morphology of neurites. Results: We first demonstrated that CRMP2 interacted with spastin to promote neurite outgrowth and branch formation. Then our results identified that CRMP2 interacted with the microtubule- binding domain of spastin via its C-terminus, and deleting these binding sites inhibited neurite outgrowth and branch formation. In addition, we confirmed one phosphorylation site at S210 of spastin in hippocampal neurons. Spastin phosphorylation at S210 failed to alter the binding affinity of CRMP2 but inhibited its binding to microtubules. Further study showed that phosphorylation spastin at S210 inhibited the neurite outgrowth induced by CRMP2 and spastin interaction through downregulation of microtubule-severing activity. Conclusion: Taken together, our data demonstrated that both CRMP2 and spastin interaction and the microtubule-severing activity of spastin were required for neurite outgrowth and branch formation.
Keywords: neurite outgrowth